The Utilization of Muara Badak Sand and Palm Kernel Shell in The Mixture for Paving Blocks - Santi Yatnikasari; Andi Wadaryanto; Adde Currie Siregar; Fitriyani Agustina (Jurnal Fondasi, 2023)
Paving block is a building material composition made from a mixture of portland cement or other hydraulic adhesives, water and aggregate with or without other additives which do not reduce the quality of the concrete. This study aims to analyze the compressive strength of paving blocks from the utilization of local sand and palm shell waste. Palm shell waste is obtained from PT. Tapian Nadenggan who processes palm oil into palm oil. The large amount of waste can be used as an added ingredient in the manufacture of paving blocks. This research method is an experimental research, by making hexagon-shaped paving blocks with a mold size of 20 cm wide, 12 cm side and 6 cm thick using estuary sand and palm oil shell ash waste with variations of 0%, 25%, 50%, 75%, 100%. The addition of ash from palm shell waste resulted in an effective compressive strength test at 28 days of age with the highest value at 50%, namely 17.64 MPa, then a 25% variation, namely 17.38% and a 75% variation with a value of 16.03%, classified as quality B can be used for parking lots. Meanwhile, the 100% variation with a yield of 11.03 MPa is included in grade D and can be used for garden.